Major Neutrophil-Derived Soluble Mediators Associate With Baseline Lung Pathology and Post-Treatment Recovery in Tuberculosis Patients - Muefong, Caleb Nwongbouwoh; Owolabi, Olumuyiwa; Donkor, Simon; Charalambous, Salome; Mendy, Joseph; Sey, Isatou C. M.; Bakuli, Abhishek; Rachow, Andrea; Geldmacher, Christof; Sutherland, Jayne S. (Frontiers in Immunology, 2021)
Background: The inflammatory response to Mycobacterium tuberculosis results in variable degrees of lung pathology during active TB (ATB) with central involvement of Neutrophils. Little is known about neutrophil-derived mediators and their role in disease severity at baseline and recovery upon TB treatment initiation. Methods: 107 adults with confirmed pulmonary TB were categorised based on lung pathology at baseline and following successful therapy using chest x-ray scores (Ralph scores) and GeneXpert bacterial load (Ct values). Plasma, sputum, and antigen-stimulated levels of MMP1, MMP3, MMP8, MMP9, MPO, S100A8/9, IL8, IL10, IL12/23(p40), GM-CSF, IFN and TNF were analyzed using multiplex cytokine arrays. Results: At baseline, neutrophil counts correlated with plasma levels of MMP8 (rho=0.45, p=2.80E-06), S100A8 (rho=0.52, p=3.00E-08) and GM-CSF (rho=0.43, p=7.90E-06). Levels of MMP8 (p=3.00E-03), MMP1 (p=1.40E-02), S100A8 (p=1.80E-02) and IL12/23(p40) (p=1.00E-02) were associated with severe lung damage, while sputum MPO levels were directly linked to lung damage (p=1.80E-03), Mtb load (p=2.10E-02) and lung recovery (p=2.40E-02). Six months of TB therapy significantly decreased levels of major neutrophil-derived pro-inflammatory mediators: MMP1 (p=4.90E-12 and p=2.20E-07), MMP8 (p=3.40E-14 and p=1.30E-05) and MMP9 (p=1.60E-04 and p=1.50E-03) in plasma and sputum, respectively. Interestingly, following H37Rv whole cell lysate stimulation, S100A8 (p=2.80E-02), MMP9 (p=3.60E-02) and MPO (p=9.10E-03) levels at month 6 were significantly higher compared to baseline. Sputum MMP1 (p=1.50E-03), MMP3 (p=7.58E-04), MMP9 (p=2.60E-02) and TNF (p=3.80E-02) levels were lower at month 6 compared to baseline in patients with good lung recovery. Conclusion: In this study, patients with severe lung pathology at baseline and persistent lung damage after treatment were associated with higher plasma and sputum levels of major pro-inflammatory neutrophil-derived mediators. Interestingly, low sputum MPO levels were associated with severe lung damage, higher Mtb burden and low recovery. Our data suggests that therapeutic agents which target these mediators should be considered for future studies on biomarkers and host-directed therapeutic approaches against TB-related lung pathology and/or lung recovery.